2016
DOI: 10.7554/elife.15175
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic potential of tumor DNA from ovarian cyst fluid

Abstract: We determined whether the mutations found in ovarian cancers could be identified in the patients' ovarian cyst fluids. Tumor-specific mutations were detectable in the cyst fluids of 19 of 23 (83%) borderline tumors, 10 of 13 (77%) type I cancers, and 18 of 18 (100%) type II cancers. In contrast, no mutations were found in the cyst fluids of 18 patients with benign tumors or non-neoplastic cysts. Though large, prospective studies are needed to demonstrate the safety and clinical utility of this approach, our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 62 publications
2
25
0
Order By: Relevance
“…Benign and malignant cysts contain statistically different levels of protein C inhibitor, apolipoprotein C‐I and C‐III, serum amyloid 4, and transthyretin . Recently, the evaluation of DNA from ovarian cyst fluid using a multiplex polymerase chain reaction‐based assay identified tumor‐specific genetic mutations not found in benign tumors or nonneoplastic cases . The mutated genes include TP53, BRAF, and KRAS, among others …”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Benign and malignant cysts contain statistically different levels of protein C inhibitor, apolipoprotein C‐I and C‐III, serum amyloid 4, and transthyretin . Recently, the evaluation of DNA from ovarian cyst fluid using a multiplex polymerase chain reaction‐based assay identified tumor‐specific genetic mutations not found in benign tumors or nonneoplastic cases . The mutated genes include TP53, BRAF, and KRAS, among others …”
Section: Discussionsupporting
confidence: 61%
“…Recently, the evaluation of DNA from ovarian cyst fluid using a multiplex polymerase chain reaction‐based assay identified tumor‐specific genetic mutations not found in benign tumors or nonneoplastic cases . The mutated genes include TP53, BRAF, and KRAS, among others …”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…For example, it has recently been shown that liquid biopsies of blood can detect minimal amounts of disease in patients with early-stage colorectal cancers, thereby providing evidence that could substantially affect their survival (7). Other studies have shown that circulating tumor DNA (ctDNA) can be detected in the blood of patients with other malignancies, as well as in other bodily fluids such as pancreatic cysts, Pap smears, and saliva (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%